Customer Service Information System Using Dynamic Priority Scheduling Algorithm At PT Sumatra Sistem Integrasi - M Fahri Aditya Nasution; Suendri; Muliani Harahap, Aninda (Ali Institute or Research and Publication, 2023)
The development of information technology can make it easier to do various things, including the provision of services that use technology in providing information to customers who need and receive information. The service at PT Sumatera Sistem Integrasi is that the process of complaining about network disturbances from customers is still manual, so that customers still come directly to the company or by telephone to make complaints and prepare reports still in the form of ledgers and customers. queues are not yet systematic and integrated. Based on these problems, the authors built a website-based customer complaint application using the Dynamic Priority Scheduling algorithm as a queue priority. The Dynamic Priority Scheduling Algorithm is a dynamic approach to the priority scheduling algorithm. In the dynamic approach, this algorithm focuses on the process of determining the queue based on predetermined priority rules. With this application, it is hoped that it can simplify and improve the quality of service to customers optimally at PT Sumatra Sistem Integrasi.